Pengaruh substitusi kulit udang dan tepung tapioka terhadap karakteristik sensoris dan fisikokimia kerupuk daun kelor: The effect of shrimp shell and tapioca flour substitution on the sensory and physicochemical characteristics of moringa leaf crackers - Indriawan, Rois; Dwi Hastuti, Ningrum; Assrorudin; Agustin, Leli (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Crackers are a type of dry, crispy snack typically made from starchy ingredients, particularly tapioca flour, due to its high starch content. However, utilizing food waste such as shrimp shells can add nutritional value while also supporting sustainable practices. Shrimp shells, a by-product of shrimp processing, contain significant levels of crude protein (25–40%), calcium carbonate (45–50%), and chitin (15–20%), making them a potential functional ingredient. This study aimed to investigate the effect of substituting shrimp shells and tapioca flour on the sensory and physicochemical characteristics of Moringa leaf crackers. The experiment was conducted using four formulations: KKU0 (0% shrimp shell: 100% tapioca), KKU1 (5%: 95%), KKU2 (10%: 90%), and KKU3 (15%: 85%). Sensory evaluations (hedonic tests) assessed color, aroma, taste, and texture, while physicochemical analyses focused on expansion (bloomability) and oil absorption. The sensory results showed that KKU3 (15% shrimp shell) had the highest preference scores: color 3.84, aroma 4.04, taste 4.36, and texture 4.52, indicating favorable consumer acceptance. However, the best physicochemical properties were observed in KKU0, with the highest bloomability (0.84%) and lowest oil absorption (0.136%), suggesting that higher shrimp shell content reduces these physical qualities. The conclusion of this study is that the substitution of shrimp shells can improve sensory acceptance, but may reduce physicochemical properties such as expansion ratio and oil absorption in moringa leaf crackers.